PERENCANAAN BERBASIS DATA DI SEKOLAH: ANTARA MIMPI TRANSFORMASI DAN REALITA IMPLEMENTASI - Sahriah; Arismunandar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT Data-Based Planning (DBP) has been promoted as a new standard for effective school management, promising efficiency and quality improvement through evidence-based decision-making. In Indonesia, this policy has been formalized through platforms such as the Education Report Card (Rapor Pendidikan), which is integrated with school budgeting systems (ARKAS). However, there remains a significant gap between the ideal expectations of DBP and the realities of its implementation in schools, where DBP is often perceived merely as an administrative burden. This article aims to critically analyze this dualism by mapping the efficiency expectations promised by DBP, identifying fundamental implementation challenges, and examining the gap between expectations and realities. This study employs a descriptive qualitative approach using a literature review method, analyzing secondary data from journals and research reports. The findings reveal that DBP theoretically offers managerial efficiency (targeted budget allocation), academic efficiency (precise quality interventions), and accountability efficiency (fact-based transparency). However, real-world implementation shows three major barriers: (1) low data literacy among school personnel, leading to a "data-rich, information-poor" phenomenon; (2) organizational cultures dominated by administrative compliance and blame culture; and (3) the absence of school principals' leadership as effective “data translators.” The gap analysis concludes that DBP failures stem not from conceptual weaknesses but from implementation issues, including (a) the emergence of an "efficiency paradox" where DBP creates new administrative burdens; (b) policy misdiagnosis that treats DBP as a technical problem (application usage) rather than an adaptive challenge (cultural and mindset change); and (c) the breakdown of the DBP logic chain at the crucial stage of root-cause analysis. The success of DBP in the future depends on shifting the focus from digital platform sophistication to investment in human capacity (data literacy) and supportive managerial leadership. Keyword; Data-Based Planning, Educational Management, Data Literacy